AN ANALYSIS OF CODE MIXING INSIDE OF WEE WEBTOON COMIC - Mayangseto, Ginarsiwi; Setyowati, Ratini (Universitas Duta Bangsa Surakarta, 2023)
There are many different countries and cultures. The way people communicate will be different according to their mother tongue. People who have an ability to use more than one language are known as bilingual. The phenomenon of bilingual in Indonesia are influential, as time passes by it created a new slang language by combining and mixing two languages to communicate and known as code-mixing. Not only by oral, this phenomenon also occurred in written and drawn which on comic inside of Webtoon platform made by Indonesian comic artist. This research study is focusing on classified the dialogue which consist of a code-mixing. By using qualitative descriptive method this research study took a subject from WEE!! comic and object which from the dialogue that contains words, sentences, and phrase of code-mixing. The result of this research found words, sentences and phrase consist of three types of code mixing; insertion, alternation, and congruent lexicalization inside of WEE!! comic.